PENGUJIAN KECENDERUNGAN KECURANGAN AKUNTANSI ORGANISASI PERANGKAT DESA DI PEMERINTAH DAERAH KABUPATEN SLEMAN - Ratna Purnama Sari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
The aim of this research is to get empirical evidence about factors influencing the tendencies of accounting fraud such as internal control, information asymmetry, the suitability of compensation, and unethical behaviour. The number of respondents selected by purposive sampling method, gaining 84 respondents filled the questionairs and worked in Organisasi Perangkat Daerah (OPD) Pemerintah Daerah Kabupaten Sleman as civil servant.  The data analized by multiple linier regression and shows that the internal control, information asymmetry, and the suitability of compensation have no effect on the accounting fraud, while unethical behavior has a significant effect on the accounting fraud.  Keywords: Internal control, information asymmetry, the suitability of compensation, unethical behavior, the tendency of accounting fraud.